2014
DOI: 10.1097/ans.0000000000000022
|View full text |Cite
|
Sign up to set email alerts
|

The Other Mother

Abstract: The purpose of this study was to develop a metastory of nonbiological lesbian mothers' postpartum experiences utilizing Riessman's structural approach to thematic analysis. Ten nonbirth lesbian mothers were interviewed. Each shared a unique story of her first year of motherhood. Themes were individually analyzed within each story. The metastory of the postpartum experiences of nonbirth lesbian mothers revealed 6 themes including the following: At the mercy of health care providers, Nursing is the major differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(84 citation statements)
references
References 17 publications
(19 reference statements)
2
82
0
Order By: Relevance
“…Thus, it appeared that there was a tendency for children to form more secure attachments to their biological than their non-biological mother. In an ethnographic study, Pelka (2009) similarly reported feelings of jealousy and being excluded by non-biological mothers in families with children born through donor insemination, Wojnar and Katzenmeyer (2014) found that non-biological mothers felt different from preconception until after the baby was born, and McKelvey (2014) highlighted the role of breastfeeding in creating a difference in the relationship between the biological and non-biological mother and the child.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it appeared that there was a tendency for children to form more secure attachments to their biological than their non-biological mother. In an ethnographic study, Pelka (2009) similarly reported feelings of jealousy and being excluded by non-biological mothers in families with children born through donor insemination, Wojnar and Katzenmeyer (2014) found that non-biological mothers felt different from preconception until after the baby was born, and McKelvey (2014) highlighted the role of breastfeeding in creating a difference in the relationship between the biological and non-biological mother and the child.…”
Section: Introductionmentioning
confidence: 99%
“…32,37,38,[40][41][42]47 Experiences were exoticized and tokenized 32 such as participants being told they were "amazing" for childbearing or "should be on Oprah," 42 partnerships were "straightened" such as assuming a partner to be a sister, 25,33,34,46 and co-parents were ignored and not recognized by providers and staff for their parental role. 46,47,50…”
Section: Erasurementioning
confidence: 99%
“…[40][41][42]45,47,50,55 The financial costs of legal fees (eg, donor contracts and second-parent adoptions) were out of reach for many and legal processes, such as second-parent adoption, are not available in all 50 states. 34,50,55 To ensure both partners' parental rights, SGD people contemplated giving birth in states with better parental rights 55 or using a sperm bank that legally terminated the donor's rights. 47 Accessing parental rights was described as a humiliating experience, 50 and the ability to protect, and even form, one's family was controlled by the ability to navigate these systems.…”
Section: Structural Exclusionmentioning
confidence: 99%
See 2 more Smart Citations